Grounded Theory and Focus Groups: Reconciling Methodologies in Indigenous Australian Education Research - Stewart, Jan (The Australian Journal of Indigenous Education, 2007)
Abstract This paper captures an ideological moment in time in which I contemplated the methodological approach I was embarking upon. In my search for a more appropriate approach for conducting research with Aboriginal and Torres Strait Islander tertiary students at the University of Queensland, I chose focus groups set within the qualitative process of grounded theory. This paper explores the meaning, usefulness and persistence of grounded theory, how it juxtaposes with focus groups, and the implications for the reciprocal integrity of the research for the Aboriginal and Torres Strait Islander students and me. Within this context and the tenets of grounded theory I ask questions such as, “For how long in the process can your research texts (linking data and theory) about field texts (participants’ narratives) remain purely inductive?” And, “How does the movement between inductive theory development and deductive assumptions fit widi issues of power and authority in an Australian Indigenous context?” I see possibility in the complementary use of grounded theory and focus groups that creates dialogic relationships between the students as both narrators and audience. Through the interaction of retelling, reliving and recreating life experiences in conversations, Aboriginal and Torres Strait Islander tertiary students conceptualise their individual subjectivities in a process of self-construction. How perceptive I am in “seeing” developing concepts within the students’ testimonies, and how I interpret those concepts in relation to existing theoretical content, may lead to new theory that influences the ongoing deconstruction of grand narratives often assigned to group identities. Co-research among the participants can provide the opportunity for monitoring the generative process.